THE ANALYSIS OF FACTORS THAT AFFECT THE DEMAND OF RED CHILI IN BLIMBING DISTRICT OF MALANG - Putri Laharwati; Khusnul Ashar (Jurnal Ilmiah Mahasiswa FEB, 2013)
The aim of this research are to To analyze the factors that influence the demand of red chili partially and simultaneously and to analyze the elasticities demand of red chili.The approach of reasearch used quantitative, with research method using multiple linier regression. While the data used are primary and secondary which taken from direct survey, related institutions, and official government website.The result shows that partially the variables of price of red chili, price of substitution good, price of complementary good, and the number of population are not significant to the demand of red chili  in Blimbing District, while  the variables of  spicy  culinary  restaurant’s income and number of spicy culinary restaurant are significant to the demand of red chili in Blimbing District. Moreover, simultaneously the variables of price of red chili, price of substitution good, price of complementary good, the number of population, spicy culinary restaurant’s income, and number of spicy culinary restaurant are significant to the demand of red chili in Blimbing District. Whereas the variables of spicy culinary  restaurant’s  income have the income elasticity value as amount 0.182 and the income elasticity for the number of spicy culinary restaurant as amount 0.323.